ANALISIS HUKUM TERHADAP PENGAMPUAN ATAS PENYANDANG DISABILITAS MENTAL (Studi Penetapan Pengadilan No. 2238/Pdt.P/2021/PN.Sby.) - Rusydi Rusydi; Shalahudddin Serba Bagus; Sholihan Sholihan; Amatus Sudin; Annafidzatul Qulub (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
Law Number 8 of 2016 concerning Persons with Disabilities states: "Persons with disabilities may be declared incompetent based on the decision of the district court." Related to these provisions, in applications for the forgiveness of mentally destabilized persons, the Applicant must follow the procedures stipulated in the laws and regulations, state the reasons, and also clearly state the Applicant and the party requested for custody (Respondent).The purpose of this study is to examine the importance of the forgiveness institution regulated in the Civil Code (KUH Perdata) and the legal consequences related to Determination Number 2238 / Pdt.P / 2021 / PN. Sby. This research is a normative legal research using a statutory approach, a concept approach, and a case approach. Legal material is taken by conducting literature research. Analysis of legal materials is carried out by quoting and reviewing relevant articles of laws and regulations. In contrast, the opinions of scholars quoted are then used as a theoretical basis to answer the subject matter.Based on the results and discussion of the legal issues raised, it can be concluded that the importance of forgiveness regulated in the Civil Code is to find out the parties related to the application for forgiveness, the type of authority of the custodian in managing the interests of the civil and the Respondent, so that there is no abuse by the custodian.